Sensitive assays for simian foamy viruses reveal a high prevalence of infection in commensal, free-ranging asian monkeys - Jones-Engel L. (2014)
Foamy viruses (FV) are retroviruses that naturally infect many hosts, including most nonhuman primates (NHPs). Zoonotic infection by primate FV has been documented in people in Asia who reported contact with free-ranging macaques. FV transmission in Asia is a concern, given abundant human-NHP contact, particularly at monkey temples and in urban settings. We have developed three assays capable of detecting the presence of FV in Asian NHP species that are commensal with humans: enzyme-linked immunosorbent assay (ELISA), Western blot assays using recombinant viral Gag protein, and an indicator cell line that can detect macaque FV. The recombinant ELISA correlates very well with the presence of FV sequences detected by PCR. We have used these assays to demonstrate both that FV is highly prevalent among free-ranging NHPs and that seroconversion occurs at a young age in these animals. These assays should also prove useful for large-scale analysis of the prevalence of FV infections in human populations in Asia that are commensal with free-ranging NHPs. Copyright © 2007, American Society for Microbiology. All Rights Reserved.